Letter: Surmounting the Roadblocks - Patricia Woo (Opticon1826, 2008)
Dr Banerjee is quite right in highlighting the roadblocks to success for women in academia. The reality for academic success depends on papers and grants and everyone, mother or not, works long hours on the way, and now that I am 60 I still put in the hours. ...
Keywords: academia; women